Le palimpseste poulinien : réécritures, emprunts, autotextualités - Gauvin, Lise (Romanica Silesiana)
The article focuses on a secret connivance between the author of “Palimpsestes” Gérard Genette and the novelist Jacques Poulin. It reveals how different modes of rewriting developed by Genette have been applied and reproduced in Poulin’s novels. The paper focuses on the rewriting of Defoe and Kerouac in “Les grandes marées” and “Volkswagen Blues”, on reference and borrowing in “La tournée d’automne” and autotextuality in “La traduction est une histoire d’amour”. Key words: novel; rewriting; theoretical surveys; Jacques Poulin